2016
DOI: 10.5303/jkas.2016.49.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Kmtnet: A Network of 1.6 M Wide-Field Optical Telescopes Installed at Three Southern Observatories

Abstract: The Korea Microlensing Telescope Network (KMTNet) is a wide-field photometric system installed by the Korea Astronomy and Space Science Institute (KASI). Here, we present the overall technical specifications of the KMTNet observation system, test observation results, data transfer and image processing procedure, and finally, the KMTNet science programs. The system consists of three 1.6 m wide-field optical telescopes equipped with mosaic CCD cameras of 18k by 18k pixels. Each telescope provides a 2.0 by 2.0 sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
194
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 283 publications
(194 citation statements)
references
References 24 publications
0
194
0
Order By: Relevance
“…Additionally, only a handful of low surface brightness dwarf galaxies have been identified from this group (Karachentsev et al 2014), while the deep multi-color stacked images obtainable in KSP are ideally suited to finding more such objects. In fact, Park et al (2016) recently identified more than 30 new dwarf galaxies in this group from the KSP data. We obtained a total of 1379 images almost equally distributed among three different bands of BV I.…”
Section: Overmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, only a handful of low surface brightness dwarf galaxies have been identified from this group (Karachentsev et al 2014), while the deep multi-color stacked images obtainable in KSP are ideally suited to finding more such objects. In fact, Park et al (2016) recently identified more than 30 new dwarf galaxies in this group from the KSP data. We obtained a total of 1379 images almost equally distributed among three different bands of BV I.…”
Section: Overmentioning
confidence: 99%
“…of optical transients. The exact coordinates of the fields are available in Park et al (2016). The NGC 2784 galaxy group was chosen because of its large sky coverage at the declination of ∼ -24.2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted photometric observations of (5247) Krylov at the three sites of KMTNet (Kim et al 2016): the Cerro-Tololo Inter-American Observatory (CTIO) in Chile, the South African Astronomical Observatory (SAAO) in South Africa, and the Siding Spring Observatory (SSO) in Australia. KMTNet consists of 1.6-m wide-field optical telescopes and 18K × 18K mosaicked CCDs with four 9K × 9K e2v chips.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Preprocessing of raw observed images was completed using the KMTNet pre-processing software (Kim et al 2016), hence crosstalk, overscan, bias and flat fielding corrections and trimming were applied. The world coordinate system (WCS) solution of the observed images is calculated using the USNO B1.0 catalog and matched with SCAMP (Bertin 2005) with an average astrometric error of 1.5…”
Section: Observations and Data Reductionmentioning
confidence: 99%